As an educator PENGEMBANGAN ASESMEN OTENTIK UNTUK MENILAI KREATIVITAS ANAK USIA DINI MELALUI PEMANFAATAN MEDIA LOOSE PART - Wiwik Mulyani; Ilham Solihin; Dwi Hastuti (STPI Bina Insan Mulia Yogyakarta, 2025)
As an educator who pursues early childhood education, of course understanding and knowing the stages and aspects of a child’s development is very important. In observing the child’s development process, of course we need accurate and precise information. Where this information can be obtained through assessment activities. There are various ways in which we can carry out these assessment activities. The method is through a formal assessment. In an early childhood education program, of course,informal assessment takes precedence over formal assessment. Especially in terms of creativity where we can maximize its potential through learing based on loose part media. This study aims to describe the developments of authentic assessments to assess students creativity through use of loose part media. This studyuses a phenomenological research method with an observation and interview approach, where to obtain the require data, the authors conduct obsevations and structured interviews. The findings in this study are that the creative potential of children can develop optimally if they receive a stimulus in the form of media that is able to support the development of creativity. Where the media is that comes from natural materials in the form of loose parts. The development of authentic assessments through the use of loose part media is very important in honing children’s creativity. Where in this learning makes the child’s psychology good and later will make the child able to maximize his potential.